Neuroimaging And Neuropsychological Studies in The Clinic Of Mild To Moderate Brain Injury (Eurasian Medical Research Periodical, 2023)
Mild to moderate traumatic brain injury (CBI) dominates the overall neurotrauma structure (80-90%). Despite a relatively good prognosis for mental recovery, in these cases, about 10-15% (according to some data, up to 30%) of patients with mild and about 50% of patients with moderate degrees of CHT develop chronic (persisting for several years after the injury) cognitive deficits.